Gene regulation and the leucine-responsive regulatory protein of Salmonella enterica serovar Typhimurium - McFarland, Kirsty A. (Trinity College (Dublin, Ireland). Department of Microbiology, 2007)
The leucine-responsive regulatory protein of Escherichia coli (E. coli) is a well characterised global regulator of transcription. Comparatively little is known about the Lrp regulon of Salmonella enterica serovar Typhimurium (S. Typhimurium ). In this study, the Irp gene was found to be regulated by nutrient availability, and negatively autoregulated, in a similar manner to that previously shown in E. coli. Autolysis o f S. Typhimurium in MOPS minimal medium was examined, and conditions that reduced autolysis were determined, which allowed for further experimentation. The regulon of Lrp was examined in S. Typhimurium , during growth in rich and nutrient poor media, using DNA microarray analysis. This revealed that Lrp regulates many genes that have previously been identified as Lrp-regulated in E. coli as well as Salmonella-specific virulence determinants, type 1 fimbriae of the fim gene cluster, and the genes of SPI-2. This also revealed genes that are affected by leucine in S. Typhimurium.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin